Silencing the voice of Bahrain? Regime-critical media and Bahrain's London diaspora. (1st April 2020) - Fibiger, Thomas
This article discusses the role of a politically mobilized diaspora in the media and politics of Bahrain. The political turmoil of several decades has resulted in the exile of a sizeable community of Bahrainis, and many key activists have settled in London. From here they continue to work with a variety of political activities and a variety of media to put pressure on both Gulf and European regimes. The article traces the development of media forms, from a print newspaper formed out of the diasporic experience, via a particular community-driven homepage opened in Bahrain in 1998, whose creator fled to London after the 2011 'Arab Spring' uprising, to the diversity of the social media that now dominates. In this regard, the role of digital surveillance, and subsequent demobilization and increasing silence, are key to the discussion.